Quantifying the percentage of methane formation via acetoclastic and syntrophic acetate oxidation pathways in anaerobic digesters. (January 2018) - Jiang, Ying; Banks, Charles; Zhang, Yue; Heaven, Sonia; Longhurst, Philip
Highlights: Dominant methanogenic pathway effectively determined by radiolabelling technique. Stoichiometric calculation to quantify percentage of CH4 formation via 2 pathways. Dominant methanogens in high NH4 + digesters found to be hydrogenotrophs. Abstract: Ammonia concentration is one of the key factors influencing the methanogenic community composition and dominant methanogenic pathway in anaerobic digesters. This study adopted a radiolabelling technique using [2- 14 C] acetate to investigate the relationship between total ammonia nitrogen (TAN) and the methanogenic pathway. The radiolabelling experiments determined the ratio of 14 CO2 and 14 CH4 in the biogas which was used to quantitatively determine the percentage of CH4 derived from acetoclastic and syntrophic acetate oxidation routes, respectively. This technique was performed on a selection of mesophilic digesters representing samples of low to high TAN concentrations (0.2–11.1 g kg −1 wet weight). In high TAN digesters, the ratio between 14 CO2 and 14 CH4 was in the range 2.1–3.0; indicating 68–75% of methane was produced via the hydrogenotrophic route; whereas in low ammonia samples the ratio was 0.1–0.3, indicating 9–23% of methane was produced by the hydrogenotrophic route. These findings have been confirmed further by phylogenetic studies.